Systemic immune‐inflammation index predicted the clinical outcome in patients with type‐B aortic dissection undergoing thoracic endovascular repair. (3rd November 2021) - Su, Sheng; Liu, Jitao; Chen, Lyufan; Xie, Enmin; Geng, Qingshan; Zeng, Hongke; Yuan, Qiong; Yang, Fan; Luo, Jianfang
Abstract: Background: The systemic immune‐inflammation index (SII) has been reported to have prognostic ability in various cardiovascular diseases; however, it has not been studied in type‐B aortic dissection (TBAD). We aimed to explore the relation of SII with short‐term and long‐term outcomes in TBAD patients undergoing thoracic endovascular repair (TEVAR). Methods: We performed a retrospective analysis of a prospectively maintained database from 2010 to 2017. The patients were divided into two groups (high SII and low SII) as per the optimal cut‐off value determined using the receiver operating characteristic curve. Multivariate logistic and Cox regression analyses were performed to analyse the relationship between the SII and the short‐term and long‐term outcomes. Results: A total of 805 TBAD patients who underwent TEVAR were enrolled. Twenty‐six (3.2%) patients died during hospitalisation. At the end of a median follow‐up duration of 48.80 mon, 70 (9.8%) patients had died. The patients were divided into the high‐SII group [ n  = 333 (41.4%%)] and the low‐SII group [ n  = 472 (58.6%)] as per the optimal cut‐off value of 1, 062. Multivariable logistic analyses showed that a high‐SII score was independently associated with major adverse cardiovascular events (MACEs) in‐hospital (odd ratio [OR], 1.67; 95% confidence interval [CI], 1.13–2.47; p  = .01). In addition, multivariable Cox analyses showed that a high‐SII score could be an independent indicator for follow‐up adverse events (hazard ratio [HR], 1.70; 95% CI, 1.14–2.56, p  = .01). Conclusions: Systemic immune‐inflammation index is associated with both in‐hospital and long‐term outcomes in patients with TBAD undergoing TEVAR. Therefore, SII may serve as valuable tool for risk stratification before intervention.